Lung transplantation for non-cystic fibrosis bronchiectasis. (June 2016) - Rademacher, Jessica; Ringshausen, Felix C.; Suhling, Hendrik; Fuge, Jan; Marsch, Georg; Warnecke, Gregor; Haverich, Axel; Welte, Tobias; Gottlieb, Jens
Abstract: Background: Lung transplantation (LTx) is a well-established treatment for end-stage pulmonary disease. However, data regarding microbiology and outcome of patients with non-cystic fibrosis bronchiectasis (NCFB) after lung transplantation are limited. Methods: A retrospective analysis between August 1992 and September 2014 of all patients undergoing lung transplantation at our program of all recipients with a primary diagnosis of bronchiectasis was performed. Microbiology of sputum and bronchoalveolar lavage specimens, lung function and clinical parameters pre- and post-LTx were assessed retrospectively. Overall survival was compared to the total cohort of lung transplant recipients at institution. The survival and development of chronic lung allograft dysfunction (CLAD) was compared in patients with and without chronic Pseudomonas aeruginosa (PSA) infection after LTx. Results: 34 patients were transplanted. Median age at transplantation was 40 (IQR 33–52) years. The most common etiologies of bronchiectasis were idiopathic (41%), chronic obstructive pulmonary disease (COPD) (21%) and post-infectious (15%). The most common organism of pre- and posttransplant chronic airway infection was PSA. One-year Kaplan-Meier survival for patients with bronchiectasis was 85% and 5-year survival was 73% and similar to the entire cohort. All three patients with an associated diagnosis of immunodeficiency died due to infection and sepsis within the first year. Patients with persistent colonization with Pseudomonas aeruginosa after transplantation had worse long-term survival by trend and developed chronic lung allograft dysfunction more frequently. Conclusions: Overall survival of patients with bronchiectasis after LTx is comparable to other underlying diseases. A reduced survival was observed in patients with the underlying diagnosis of immunodeficiency. Highlights: The outcome of lung transplantation for bronchiectasis is comparable to other conditions with regard to survival and CLAD-free survival. Inferior results were observed in patients with the underlying diagnosis of immunodeficiency. The presence of chronic PSA infection leads to shorter survival times by trend.